2016
DOI: 10.1002/mbo3.417
|View full text |Cite
|
Sign up to set email alerts
|

Keeping it in the family: Coevolution of latrunculid sponges and their dominant bacterial symbionts

Abstract: The Latrunculiidae are a family of cold water sponges known for their production of bioactive pyrroloiminoquinone alkaloids. Previously it was shown that the bacterial community associated with a Tsitsikamma sponge species comprises unusual bacterial taxa and is dominated by a novel Betaproteobacterium. Here, we have characterized the bacterial communities associated with six latrunculid species representing three genera (Tsitsikamma, Cyclacanthia, and Latrunculia) as well as a Mycale species, collected from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 71 publications
1
61
0
Order By: Relevance
“…The gut tissue of A. agassizii was dominated by Spirochaetia, mostly represented by the genus Spirochaeta which was prevalent in all of the samples and accounted for as much as 80% relative abundance of the class. Spirochaetes are motile freeliving, facultative/obligate anaerobes (Leschine et al, 2006), associated with numerous marine invertebrates, among others, corals (Lawler et al, 2016;Van De Water et al, 2016), sponges (Matcher et al, 2017;Kellogg, 2019), sea stars (Jackson et al, 2018), and at the body surface of the regular sea urchin species Tripneustes gratilla (<15% relative abundance) (Brink et al, 2019). Such a prevalence inside the gut of a sea urchin has never been described and suggests a specific interaction between Spirochaeta and the Abatus host.…”
Section: Spirochaeta and Desulfobacula: Keystones Of The Abatus Micromentioning
confidence: 99%
“…The gut tissue of A. agassizii was dominated by Spirochaetia, mostly represented by the genus Spirochaeta which was prevalent in all of the samples and accounted for as much as 80% relative abundance of the class. Spirochaetes are motile freeliving, facultative/obligate anaerobes (Leschine et al, 2006), associated with numerous marine invertebrates, among others, corals (Lawler et al, 2016;Van De Water et al, 2016), sponges (Matcher et al, 2017;Kellogg, 2019), sea stars (Jackson et al, 2018), and at the body surface of the regular sea urchin species Tripneustes gratilla (<15% relative abundance) (Brink et al, 2019). Such a prevalence inside the gut of a sea urchin has never been described and suggests a specific interaction between Spirochaeta and the Abatus host.…”
Section: Spirochaeta and Desulfobacula: Keystones Of The Abatus Micromentioning
confidence: 99%
“…In a previous study we found no evidence of seasonal variation in the bacterial communities associated with Tsitsikamma favus sponges collected from Evans Peak [27]. Furthermore, a statistical analysis of the bacterial communities from four seawater samples collected at Evans Peak between August 2014 and June 2016 showed that there was no significant difference ( p = 0.71) between them (S.H.…”
Section: Discussionmentioning
confidence: 75%
“…In an effort to unequivocally establish the biosynthetic origin of the tsitsikammamines, a detailed community structure analysis of the symbiotic bacteria found in T. favus sponges collected from Algoa Bay is currently underway at Rhodes University. 9,33 The microbial community analyses are coupled to a metagenomic search for microbial biosynthetic gene clusters that might ultimately be responsible for the biosynthesis of the tsitsikammamines. The structural novelty and bioactivity of the tsitsikammamines has attracted interest from synthetic chemists and tsitsikammamine A was first synthesised by Delfourne and co-workers.…”
Section: Figurementioning
confidence: 99%